2017
DOI: 10.1371/journal.pone.0180614
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat reference values derived from healthy European men and women aged 20-30 years using GE Healthcare dual-energy x-ray absorptiometry

Abstract: Dual energy X-ray absorptiometry (DXA) is an established technique used in clinical and research settings to evaluate total and regional fat. Additionally, recently developed software allow to quantify visceral adipose tissue (VAT). Currently, there are no reference values available for GE Healthcare DXA systems for VAT. The aim of this study was to develop reference values for VAT in healthy European adults aged 20–30 years using a GE Healthcare Prodigy densitometer along with the dedicated CoreScan applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 24 publications
8
58
5
Order By: Relevance
“…27,28 More recently, different cutoff scores of VAF were established for men (≥599 cm 3 ) and women (≥399 cm 3 ) as a predictor for systolic blood pressure ≥130 mmHg in healthy young European population using DEXA method. 29 In our study, VAF volume values differ from those reported in Japanese and European populations. In the available literature, we did not find previously standardized values of VAF in the world or Mexican population apart from those reported in the European and Japanese population.…”
Section: Discussioncontrasting
confidence: 91%
“…27,28 More recently, different cutoff scores of VAF were established for men (≥599 cm 3 ) and women (≥399 cm 3 ) as a predictor for systolic blood pressure ≥130 mmHg in healthy young European population using DEXA method. 29 In our study, VAF volume values differ from those reported in Japanese and European populations. In the available literature, we did not find previously standardized values of VAF in the world or Mexican population apart from those reported in the European and Japanese population.…”
Section: Discussioncontrasting
confidence: 91%
“…Similar or even higher rates were found among young white participants in the CARDIA Study (32%), Jackson Heart Study (73%), and African‐PREDICT Study (34%) . A novel finding of our study is that VF, known to be strongly associated with a range of metabolic abnormalities even in healthy individuals, is also suggested here to have had an impact on the magnitude of fall in nocturnal blood pressure. VF (expressed as mass percentage), after adjusting for confounders, was found associated with an absence of physiological nocturnal fall in SBP.…”
Section: Discussionsupporting
confidence: 80%
“…Here, we used this method for the first time in a population of young adults with hypertension. Using our pre‐defined age‐ and gender‐specific VF reference values derived from the healthy population, we found excess VF mass in 52% of males and 47% of females. DXA‐VF was a relatively small fat depot, which constituted only 1.5% of patient weight and 3.1% of TBF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral adipose tissue assessed with different techniques has emerged as a potential marker to evaluate cardio metabolic risk 4,14,[17][18][19][20] . It has been shown that DXA is an adequate tool to assess this parameter 5,14,17,21 . The study by Kaul et al 5 reported that VAT evaluated by DXA had a moderate correlation with AC and weak correlation with BMI and WHR.…”
Section: Discussionmentioning
confidence: 99%